Fluorescence quenching and time-resolved fluorescence studies of alpha-Mannosidase from Aspergillus fischeri (NCIM 508) - Shashidhara, K. S.; Gaikwad, Sushama M. (Journal of Fluorescence, 2007)
Apart from the vital role in glycoprotein biosynthesis and degradation, alpha-mannosidase is currently an important therapeutic target for the development of anticancer agents. Fluorescence quenching and time-resolved fluorescence of alpha-mannosidase, a multitryptophan protein from Aspergillus fischeri were carried out to investigate the tryptophan environment. The tryptophans were found to be differentially exposed to the solvent and were not fully accessible to the neutral quencher indicating heterogeneity in the environment. Quenching of the fluorescence by acrylamide was collisional. Surface tryptophans were found to have predominantly positively charged amino acids around them and differentially accessible to the ionic quenchers. Denaturation led to more exposure of tryptophans to the solvent and consequently in the significant increase in quenching with all the quenchers. The native enzyme showed two different lifetimes, tau (1) (1.51 ns) and tau (2) (5.99 ns). The average lifetime of the native protein (tau) (3.187 ns) was not affected much after denaturation (tau) (3.219 ns), while average lifetime of the quenched protein samples was drastically reduced (1.995 ns for acrylamide and 1.537 ns for iodide). This is an attempt towards the conformational studies of alpha-mannosidase.
Keywords: alpha-Mannosidase; Denaturation; fluorescence; lifetime; Solute quenching

Steady state and time-resolved fluorescence studies of a hemagglutinin from Moringa oleifera - Katre, Uma V.; Suresh, C. G.; Khan, Mohammad Islam; Gaikwad, Sushama M. (Journal of Fluorescence, 2008)
The saccharide binding and conformational characterization of a hemagglutinin, a low molecular weight protein from the seeds of Moringa oleifera was studied using steady state and time resolved fluorescence. The lectin binds sugars LacNAc (K-a = 1380 M-1) and fructose (K-a = 975 M-1), as determined by the fluorescence spectroscopy. It has a single tryptophan per monomer which is exposed on the surface and is in a strong electropositive environment as revealed by quenching with iodide. Quenching of the fluorescence by acrylamide involved both static (K-s = 0.216 M-1) and collisional (K-sv= 8.19 M-1) components. The native protein showed two different lifetimes, tau(1) (1.6 ns) and tau(2) (4.36 ns) which decrease and get converted into a single one, (2.21 ns) after quenching with 0.15 M acrylamide. The bimolecular quenching constant, k(q) was 7.55 x 10(11) M-1 s(-1). ANS binding studies showed that the native protein has exposed hydrophobic patches which get further exposed at extreme acidic or alkaline pH. However, they get buried in the interior of the protein in presence of 1 M GdnHCl or urea.
Keywords: ANS binding; fluorescence; Hemagglutinin; lifetime; Moringa oleifera; saccharide binding; Solute quenching

Aromatic amine passivated TiO2 for dye-sensitized solar cells (DSSC) with similar to 9.8% efficiency - Kumar, T. R. Naveen; Yuvaraj, S.; Kavitha, P.; Sudhakar, Vediappan; Krishnamoorthy, Kothandam; Neppolian, B. (Solar Energy, 2020)
In this work, the efficiency of dye-sensitized solar cells (DSSC) was improved by capping TiO2 with simple aromatic amines as a complexing agent. The aromatic amines, aniline and o-phenylenediamine capped TiO2 composites were synthesized via hydrothermal route and used as scattering layer in dye-sensitized solar cell (DSSC). Markedly, the maximum photo-conversion efficiency of 9.84% was achieved with o-phenylenediamine capped-TiO2 composite as o-phenylenediamine capped-TiO2 showed higher reflectivity than the pristine TiO2, which is highly beneficial for reflecting the photons back to photoanode. In addition, the average life time of carriers in o-phenylenediamine capped-TiO2 was found to be 9.8 ms, which was 2 times higher than the pristine TiO2 (4.29 ms).
Keywords: Aromatic amines; DSSC; Electron injection; lifetime; Scattering layer; TiO2